Informação, educação patrimonial e museus no ciberespaço: diálogos - Clotildes Madalena de Avelar Teixeira (2014)
The aim of this research, based on the dialogue among information, technology, museum, cultural heritage and memory, was done to capture the potentialities of these contributions for the education heritage and the proposals of a virtual museum. It was carried out having as an empiric fundament the Ofício das Paneleiras de Goiabeiras in Vitória, Espírito Santo State, the first Brazilian cultural asset to be recognized as an intangible cultural heritage. The methodology used was to map the virtual museums proposals and rescue the memory of the capixabas craftsmanship using semi-structured interviews and the oral history. Theresearch obtained as its results the reconstitution of the craftsmanship, the significance of the work for the group and comprehended the participation of the different actors for the Oficio das Paneleiras as a cultural assets. Based on these results and having as referencethe researched data, a proposal for Virtual Museum (MUVI) was elaborated as a contribution to the and the safeguard intangible cultural heritage.